The 2017 international classification of the Ehlers–Danlos syndromes. Issue 1 (March 2017) - Malfait, Fransiska; Francomano, Clair; Byers, Peter; Belmont, John; Berglund, Britta; Black, James; Bloom, Lara; Bowen, Jessica M.; Brady, Angela F.; Burrows, Nigel P.; Castori, Marco; Cohen, Helen; et al.
Abstract : The Ehlers–Danlos syndromes (EDS) are a clinically and genetically heterogeneous group of heritable connective tissue disorders (HCTDs) characterized by joint hypermobility, skin hyperextensibility, and tissue fragility. Over the past two decades, the Villefranche Nosology, which delineated six subtypes, has been widely used as the standard for clinical diagnosis of EDS. For most of these subtypes, mutations had been identified in collagen‐encoding genes, or in genes encoding collagen‐modifying enzymes. Since its publication in 1998, a whole spectrum of novel EDS subtypes has been described, and mutations have been identified in an array of novel genes. The International EDS Consortium proposes a revised EDS classification, which recognizes 13 subtypes. For each of the subtypes, we propose a set of clinical criteria that are suggestive for the diagnosis. However, in view of the vast genetic heterogeneity and phenotypic variability of the EDS subtypes, and the clinical overlap between EDS subtypes, but also with other HCTDs, the definite diagnosis of all EDS subtypes, except for the hypermobile type, relies on molecular confirmation with identification of (a) causative genetic variant(s). We also revised the clinical criteria for hypermobile EDS in order to allow for a better distinction from other joint hypermobility disorders. To satisfy research needs, we also propose a pathogenetic scheme, that regroups EDS subtypes for which the causative proteins function within the same pathway. We hope that the revised International EDS Classification will serve as a new standard for the diagnosis of EDS and will provide a framework for future research purposes. © 2017 Wiley Periodicals, Inc.